The practical application of automatic vision alignment to the Internet of Things production line. (April 2017) - Zou, Chengming; Xu, Xiaolong
This paper presents a new system in which automatic Vision Alignment was applied to the Internet of Things (IoT) production line to solve the problem of automatic assembling of screws and iron plates with holes. The position of screw holes are searched for by Machine Vision and transmitted to the robotic arm so that it could insert screws into holes. During this process, a swarm intelligence algorithm – Adaptive Multi-elite Wolf Pack Algorithm (AMWPA) – was used to recognize the holes. The experimental results show that the algorithm succeed in recognizing holes and has better global convergence and computational robustness.